(untitled) (BIRDEM Medical Journal, 2021)
Background: Cerebral palsy (CP) is the most common developmental disability in children. Neuro-imaging in CP is widely used investigation. Imaging study can visualize the anatomical location of lesion in brain. The aim of this study was to find out the extent of non-progressive damage in brain among children with CP. Methods: This was a cross-sectional study. Data were collected from the out-patient department of Institute of Pediatric Neurodisorders & Autism (IPNA), Bangabandhu Sheikh Mujib Medical University (BSMMU) from December, 2019 to March, 2020. Results: Total 88 cases (age up to 14 years) were reviewed. There was male predominance and male to female ratio was 2:1. Computed tomography (CT) scan was done in majority of patients (71 cases) and magnetic resonance imaging (MRI) in 17 cases. Major abnormalities were atrophy in 34.1% cases, ventricular dilatation in 14.8% cases, encephalomalacia in 19.3% cases and basal ganglia lesion in 11.4% cases. Overall in CT scan group, 95.77% cases were abnormal and in MRI group, 88.23% were abnormal. Conclusion: Atrophy of the brain was the most common finding in neuro-imaging of patients with CP and developmental disabilities. Neuro-imaging is very useful and recommended for the children with developmental delay and CP cases. It may help to classify the CP and may give a clue for further investigations such as metabolic screening and genetic testing. Birdem Med J 2021; 11(2): 112-115